2021
DOI: 10.1186/s13071-021-04661-1
|View full text |Cite
|
Sign up to set email alerts
|

Diphyllobothrium sprakeri n. sp. (Cestoda: Diphyllobothriidae): a hidden broad tapeworm from sea lions off North and South America

Abstract: Background The systematic of several marine diphyllobothriid tapeworms of pinnipeds has been revised in recent years. However, 20 species of Diphyllobothrium from phocids and otariids are still recognized as incertae sedis. We describe a new species of Diphyllobothrium from the intestine of California sea lions Zalophus californianus (Lesson) (type-host) and South American sea lions Otaria flavescens (Shaw). Methods Zalophus californianus from the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 44 publications
(45 reference statements)
0
2
0
Order By: Relevance
“…2a ). Molecular identification using two of these strobilae, following methods described in previous studies [ 8 , 16 ], showed 100% and 99.78% identities with the sequences of Diphyllobothrium sp. During the autopsy, four larvae of a cestode ( Clisthobothrium delphini ) were obtained from the blubber tissue.…”
mentioning
confidence: 72%
“…2a ). Molecular identification using two of these strobilae, following methods described in previous studies [ 8 , 16 ], showed 100% and 99.78% identities with the sequences of Diphyllobothrium sp. During the autopsy, four larvae of a cestode ( Clisthobothrium delphini ) were obtained from the blubber tissue.…”
mentioning
confidence: 72%
“…PCR were performed as described by . Sequences of the cox2 and cox1 genes have a high resolving power to identify species in anisakids and metacestodes, respectively, while the 28S rRNA gene sequences can be used as a marker for analysis of evolutionary events at the genus level and above (e.g., Mattiucci and Nascetti 2008;Hernández-Orts et al 2021).…”
Section: Molecular Datamentioning
confidence: 99%